Identification of Thalictrum squarrosum as an alternate host for Puccinia triticina and pathogen analysis of Thalictrum squarrosum rust - Zhao, Na; Huang, Liang; Ren, Jun; Zhang, Mengya; Yi, Ting; Li, Hongfu; Zhang, Hao; Liu, Bo; Gao, Li; Yan, Hongfei; Chen, Wanquan; Liu, Taiguo (Frontiers in Plant Science, 2025)
Puccinia triticina (Pt) is a heteroecious fungus needing two different plants as primary and alternate hosts throughout its life cycle. Thalictrum spp. were first identified as alternate hosts of Pt in 1921, and over 100 species have been identified. However, within China, only T. petaloideum L., T. minus L., T. minus var. hypoleucum and T. baicalense have been reported as alternate hosts of Pt. During the six-year (2015-2018, 2023-2024) field surveys in Zhangbei County (41.26°N, 115.14°E), Zhangjiakou City, Hebei Province, our research team found rust disease on T. squarrosum. This persistent infection phenomenon aroused our interest in investigating the role of T. squarrosum in the sexual reproduction of pt. To clarify whether T. squarrosum can serve as an alternate host for Pt and to analyze the source of the pathogen, this study used artificial inoculation experiments and molecular identification techniques. The results of the artificial inoculation experiments showed that the basidiospores of Pt could infect T. squarrosum, and produce pycnia on the adaxial surface of the leaf. Subsequently, aecia were produced on the abaxial side of the leaf after artificial fertilization, and the mature aecia produced aeciospores. The aeciospores were then inoculated into susceptible wheat varieties and the wheat showed typical symptoms of wheat leaf rust. These results confirmed that T. squarrosum could serve as an alternate host for Pt. For molecular identification, 20 single-aecium samples of T. squarrosum were selected. Based on sequence alignment of their ITS regions and phylogenetic analysis, it was shown that rust on T. squarrosum could be caused by infection of Pt from wheat or the species complex of P. recondita. Our study provides new insights into the sexual cycle of Pt in China and provides a scientific basis for studying the evolution of Pt virulence and optimizing control methods for wheat leaf rust.